Orange Agro-Edutourism Development Strategy in Samar Village: An Effective and Appropriate Approach to Improve the Local Economy - Pebrianto, Moh.; Yuliati, Yayuk; Kustanti, Asihing (Universitas Panji Sakti, 2025)
The Citrus Agroedutourism in Samar Village is an effort to optimize local potential by integrating agricultural education with community-based tourism. Despite its strong appeal, this destination faces several challenges, including weak management, limited digital promotion, a shortage of skilled human resources, and inadequate infrastructure. This study aims to analyze the most effective and appropriate development strategies to support sustainable local economic growth. This research adopts a mixed-method approach, with data collected through in-depth interviews, field observations, documentation, and literature review. Data were analyzed using thematic analysis to identify core themes from participant narratives, which were then mapped into a qualitative SWOT quadrant to formulate context-based development strategies. The findings indicate that Samar Village's main strengths lie in its unique citrus commodity, strong community involvement, and educational tourism appeal. However, weaknesses such as limited expertise, minimal promotion, and financial constraints hinder development. The recommended strategies include human resource training, infrastructure improvement, digital branding enhancement, and multi-stakeholder collaboration involving the village government, BUMDes, and youth organizations. The study concludes that citrus-based agroedutourism has strong potential to serve as a model for sustainable village development that effectively contributes to improving community welfare. These findings offer important managerial implications, including the need for strategic planning based on local potential, institutional capacity building, and the integration of environmental sustainability, community empowerment, and educational tourism promotion.